Segmentation of Ecotourists in Pahang National Park Based on Travel and Motivation Attributes - Abdul Rashid, Rosmalina (2005)
The success of a national park as an ecotourism site depends on the visitation of ecotourists. The physical and social impacts of mass tourist at the Taman Negara (Pahang) National Park may invite conflicts between ecotourists and other tourists. The purpose of the present study was to segment ecotourists based on their motivations of visits in order to understand the conflicts among ecotourist. This study eventually leads to behavioural differences related to their ecotourism attributes. Multiple Discriminant Analysis (MDA) test was administered to segment and predict ecotourist types. A total of 389 respondents were studied using convenience sampling design. From the analysis, the ecotourists in Kuala Tahan, Taman Negara (Pahang) National Park were consequently segmented into (1) Hard-Core ecotourists, (2) Mainstream ecotourists, (3) Dedicated ecotourists, and (4) Casual ecotourists. The ecotourist groups were then differentiated by fourteen variables of motivational items and three variables of travel characteristics using the discriminant function analysis. Function 1, labelled as freedom of choice, which made up of motivation factors include knowledge, lifestyle, adventure and novelty, while Function 2 was labelled as wisdom for pursuing travel, which include leisure and travel characteristics of ecotourists. The Multiple Discriminant Analysis model has shown that there were several relationships between ecotourist types and motivations and travel characteristic variables. Nevertheless, the ecotourists segmentation procedure showed that there was variation in terms of their awareness towards ecotourism attributes namely nature, learning and education, environment, and socio-cultural consciousness. Hard-core ecotourists were revealed as “true” ecotourists compared to the other types of ecotourists because they placed higher importance upon nature learning and education and environmental consciousness. Because distinctively different ecotourist types exist at the park, management and promotional efforts should also be approached and implemented differently by the Park’s management and authority in order to fulfill the needs of the different types of ecotourists, specifically the Hard-core ecotourists. The practice should also be parallel to the country’s objectives of the Park’s nature conservation. Here, the inclination of the Hard-core ecotourists toward nature necessitates more nature in-depth and cultural programmes.